2020
DOI: 10.3390/su12198106
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of the Relation between Human and Environmental Wellbeing in Different Stages of National Development

Abstract: The literature formed around the concept of sustainable development emphasizes that its achievement depends on how its dimensions evolve. Considering that the economic dimension is not an end in itself, but a means for achieving the other two dimensions, we concentrated on the relation between environment and society. Using the framework of Sustainable Society Index, we applied path analysis for identifying the effects of human wellbeing components on environmental wellbeing for 71 countries around the world i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…Such an attitude should represent a moral and civic obligation, especially for the people involved in decision-making processes. This finding is consistent with that of Seifi [ 73 ], Stratan et al [ 108 ], Ulman et al [ 53 ], or Ulman et al [ 22 ]. These authors also emphasized the role of good governance for avoiding environmental degradation, as well as the need for more pro-environmentally oriented policies.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Such an attitude should represent a moral and civic obligation, especially for the people involved in decision-making processes. This finding is consistent with that of Seifi [ 73 ], Stratan et al [ 108 ], Ulman et al [ 53 ], or Ulman et al [ 22 ]. These authors also emphasized the role of good governance for avoiding environmental degradation, as well as the need for more pro-environmentally oriented policies.…”
Section: Resultssupporting
confidence: 92%
“…Human wellbeing is defined as formed by nine components (see Van de Kerk and Manuel [ 21 ], as well as Kowalski and Veit [ 50 ]), analyzed in the literature in relation to the environment, as follows: sufficient amount of food [ 51 , 52 , 53 ], sufficient to drink [ 54 , 55 , 56 ], safe sanitation [ 22 , 53 , 57 ], education [ 22 , 53 , 58 , 59 ], health [ 22 , 53 , 60 , 61 , 62 ], gender equality [ 21 , 23 , 63 , 64 ], income distribution [ 20 , 22 , 53 , 65 , 66 , 67 ], population growth [ 53 , 68 , 69 , 70 , 71 ], and good governance [ 22 , 53 , 59 , 72 , 73 , 74 ] (see Table 2 ). For example, it was demonstrated that (1) the lack of safe sanitation represents a pollutant factor, negatively influencing environmental wellbeing [ 22 , 57 ], (2) the level of individual education registers positive effects on pro-environmental attitudes [ 58 , 59 , 75 ], while the number of students enrolled in education may influence enviro...…”
Section: Introductionmentioning
confidence: 99%
“…In this way, energy savings and renewable energy, evaluated in terms of levels of wellbeing, are put face to face with the indicators of human and economic wellbeing and analyzed from the perspective of their effects on them. More clearly, as shown in previous studies (Ulman et al, 2021a(Ulman et al, , 2021bUlman et al, 2020), positive relationships could be able to reveal a sustainable path of development as human and economic components prove to be able of overcoming the most common way of influence, i.e. a negative one in relation to environment.…”
Section: Source: Authors' Representation Ssi Databasementioning
confidence: 58%
“…the components of SSI), were linked to diverse social and economic issues in order to understand their implications towards environmental degradation. For example, Ulman et al (2020;2021) tried to observe the nature of influence among, on one hand, environmental and economic components and, on the other hand, environmental and social components of wellbeing in different contexts, i.e. the European Union and the Central and Eastern European Countries, while also considering the stages of development of the analyzed countries in order to understand the type of development put into practice across these groups of countries.…”
Section: Ecological Footprint Minus Carbon Footprint Once It Is Alrea...mentioning
confidence: 99%
“…However, recent decades have made people realize that there are processes accompanying economic growth, having a negative impact on the natural environment and social relations, including increasing economic inequalities [1]. Therefore, thinking about growth in terms of sustainable growth begins to predominate, where human needs are met in such a way as not to diminish the chances of realizing the needs of future generations [2].…”
Section: Introductionmentioning
confidence: 99%